Effect of nitrogen rates on growth and quality of water spinach (Ipomea aquatica) - Ibrahim, Mohd Hafiz; Abdul Rahman, Nurhafizah Yasmin; Mohd Zain, Nurul Amalina (SCIENCEDOMAIN International, 2018)
Aims: The study was conducted to investigate the impact of nitrogen fertilization on growth, leaf gas exchange and bio-metabolite accumulation in Ipomea aquatica. Treatment and Experimental Design: Ipomea aquatica plants were exposed to four different rates of nitrogen (0, 30, 60 and 90 N kg/ha) using Urea (46% N) as a nitrogen source. The experiment was laid out in Complete Randomize Design (CRD). Place and Duration of Study: Department of Biology, Faculty of Science, Universiti Putra Malaysia between September to November 2016. Methodology: Four nitrogen rates were applied (0, 30, 60 and 90 N Kg/ha) using Urea as a nitrogen source. The growth data collections were conducted once a week after the application of the treatments for the plant growth parameters. The total chlorophyll content in the leaves was measured using a Soil Plant Analytical Device (SPAD-502) chlorophyll meter. The leaf gas exchange was determined using a LI-6400XT portable photosynthesis system. Total phenolics and flavonoid were determined using Folin-Ciocalteu reagent.